Guinea : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The statistical data on gross domestic product, consumer price index, financial operations of the central government, central government revenue and expenditure, monetary survey, summary accounts of the central bank, summary accounts of deposit money banks, sectoral distribution of credit, quarterly distribution of credit by sector and maturity, and structure of interest rates of Guinea are presented in this paper. The data on balance of payments, composition of merchandise exports, direction of trade, external public debt, and related economic indices are also presented.